Enhancement in photostability of betalain dye from basella Alba fruits using zinc oxide nanoparticles. (2022) - Muthulingam, S.; Greeshma, K.P.; Poornima, K.; Tamizselvi, R.; John, Sam; Uthirakumar, A.P.
Abstract: Recently environmental pollution due to industrial effluents is a major concern for researchers, so the development of natural dyes is widely accepted due to their low cost, biodegradability, low toxicity, and non -carcinogenic nature and also replaces existing hazardous chemicals in industries. Many plants and fruit extracts can be used as natural dyes, but their efficiency depends on photostability and photo degradation activity. Herein reported extraction of natural dye from Basella Alba fruit using different solvents and photo stability was investigated under UV and visible light. To enhance the stability of extracted pure dye, zinc oxide nanoparticles were added and it acts as an excellent photostabilizer that shows better performance over betalain dye. UV visible spectrum of pure dye shows an absorbance peak of 480 nm and functional groups of both dye and zinc oxide were identified by FTIR spectrum. The structure and surface morphology of the synthesized nanoparticle was confirmed by UV–Visible, XRD, SEM-EDAX and TEM analysis. The crystalline structure of zinc oxide was confirmed by XRD and composition was analyzed by EDAX studies. The wurtzite type structure of zinc nanoparticle was confirmed by XRD. The external morphology of prepared zinc oxide nanoparticles is captured using FESEM. The HRTEM and SAED images are confirmed the crystalline structure of the synthesized material. The photostability and photodegradation studies were performed under UV light and at various temperatures like 40 °C, 50 °C, 60 °C, 70 °C, and 80 °C. These results clearly show a piece of evidence for the usage of nanoparticles for enhancing photostability of natural dyes.